Traditional Massallo Game Approach Model in Elementary School: Foot Reaction Speed in Badminton - Sukardi, Sulham; Suwardi, Suwardi; Hudain, Muh. Adnan; Adil, Ahmad; Fahrizal, Fahrizal (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to improve the reaction speed of the feet in badminton through the traditional massalo game approach in students of elementary school. The study employed Classroom Action Research, which involved two cycles of planning, action implementation, observation, and reflection. The population and sample of the study were all grade V students of elementary school 171 Pinrang, totaling 20 students. The results of the study showed a significant increase from the pre-cycle to cycle II. In the pre-cycle, 100% of students were in the less category (score < 80) with 0% completion. Cycle I showed an increase, with 50% of students achieving completion in the sufficient category (score ≥ 80-86). In cycle II, after changes were made to the Massaro game approach, every student (100%) completed the tasks in the sufficient category, with their average reaction time increasing by 35% and their active participation reaching 95%. In conclusion, the traditional massalo game approach has proven effective in improving the reaction speed of the feet in badminton while creating a positive and enjoyable learning experience for elementary school students.